International Symposium for Intelligent Transportation and Smart City (ITASC) 2017 proceedings : branch of ISADS (The International Symposium on Autonomous Decentralized Systems) /: branch of ISADS (The International Symposium on Autonomous Decentralized Systems). ([2017]) - Unknown
No abstract available